KONSEP PENIDIDIKAN ISLAM MODERN-KONTEKSTUAL HAJI RASUL - Yuli habibatul imamah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
Talking about modern Islamic education, especially in Indonesia, it should not pass the chapter on Haji Rasul and the educational institutions he founded. Because during the confinement of conventional education patterns in pre and early independence, he with his Sumatra Thawalib became a pioneer who brought fresh air and became a milestone in the birth of modern education in the subsequent journey of Islamic education. Sumatra Thawalib, which was originally a traditional educational institution that applied conventional education patterns and curriculum, was able to be transformed by Haji Rasul into a modern educational institution that was professionally managed by a school committee, no longer owned by individuals. The learning pattern that was originally in the form of halaqah as is generally found in traditional educational institutions, was overhauled by applying a learning pattern that uses a class system for leveling and differentiating learning materials. This paper seeks to explore the ideas of Haji Rasul's Islamic education that led to the establishment of Sumatra Thawalib in Minangkabau. What was the background and influenced the concept of his educational thought, as well as how the pattern of learning and school organization applied in Sumatera Thawalib, became the central point of discussion of this paper.